Massive postvaginoplasty retrovaginal hematoma: A case report (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Case presentation: A para 4+0 with a history repeated of macrosomic fetuses and four subsequent spontaneous vaginal deliveries highlighted by third- and fourth-degree perineal tears presented with vaginal laxity requiring surgical vaginoplasty. Postoperatively, she developed acute urinary retention, weakness, lethargy, and pallor and was noted to have a massive posterior vaginal wall hematoma, which was soon evacuated, and vaginoplasty was successfully revised.Discussion: Urinary retention is a unique symptom of retrovaginal hematoma, but it must be considered following vaginoplasty. During vaginoplasty, the posterior vaginal wall expands to abut the anterior vaginal wall and inferior urethral wall, preventing evacuation of the bladder. The posterior vaginal wall is elastic and able to discretely accommodate a large amount of blood loss with no signs of vaginal bleeding and should be a point of examination following vaginoplasty.Conclusion: The expected signs and symptoms of vaginoplasty complications are vaginal bleeding and perineal tenderness. Urinary retention, pallor, and other signs can indicate a retrovaginal hematoma. Cosmetic gynecology practitioners should consider the elasticity and discreetness of the posterior vaginal wall and its ability to accommodate massive hematomas with few signs.